Análisis de la cultura tributaria y su incidencia en la facturación electrónica de los contribuyentes de la ciudad de Calceta - Álava Zambrano, Joseph Steeven (2024)
The objective of this research was to analyze the tax culture in order to determine the incidence of electronic invoicing of taxpayers in the city of Calceta, period 2021-2022. The methodology used included the survey technique applied to 372 taxpayers, as well as an interview with the Director of the SRI of Portoviejo, in order to determine the incidence of the tax culture of taxpayers in the city of Calceta on the electronic invoicing carried out. Inductive-deductive, analytical-synthetic and comparative research methods were employed to approach the study problem in a logical manner. The results revealed a deeper understanding of the requirements, obligations and procedures established by the tax authorities, as well as the restrictions, penalties and benefits associated with electronic invoicing. The survey revealed that the majority of taxpayers (60%) agree with the mandatory use of electronic invoicing, although 51% indicated a lack of support in terms of training by the IRS regarding electronic invoicing. The interview with the Director of the SRI confirmed that electronic invoicing strengthens the tax culture by promoting transparency and awareness of tax compliance, in addition to having a positive impact on tax collection. Finally, strategies are proposed to foster a greater tax culture and promote the adoption of electronic invoicing among taxpayers.